Winner or loser of climate change? A modeling study of current and future climatic suitability of Arabica coffee in Indonesia - Schroth, Götz; Läderach, Peter R.D.; Blackburn Cuero, Diana Sofia; Neilson, Jeffrey; Bunn, Christian (Springer, 2015)
Previous research has shown that the production of Arabica coffee (Coffea arabica), the main source of high-quality coffee, will be severely affected by climate change. Since large numbers of smallholder farmers in tropical mountain regions depend on this crop as their main source of income, the repercussions on farmer livelihoods could be substantial. Past studies of the issue have largely focused on Latin America, while the vulnerability of Southeast Asian coffee farmers to climate change has received very little attention. We present results of a modeling study of climate change impacts on Arabica coffee in Indonesia, one of the world’s largest coffee producers. Focusing on the country’s main Arabica production zones in Sumatra, Sulawesi, Flores, Bali and Java, we show that there are currently extensive areas with a suitable climate for Arabica coffee production outside the present production zones. Temperature increases are likely to combine with decreasing rainfall on some islands and increasing rainfall on others. These changes are projected to drastically reduce the total area of climatically suitable coffee-producing land across Indonesia by 2050. However, even then there will remain more land area with a suitable climate and topography for coffee cultivation outside protected areas available than is being used for coffee production now, although much of this area will not be in the same locations. This suggests that local production decline could at least partly be compensated by expansion into other areas. This may allow the country to maintain current production levels while those of other major producer countries decline. However, this forced adaptation process could become a major driver of deforestation in the highlands. We highlight the need for public and private policies to encourage the expansion of coffee farms into areas that will remain suitable over the medium term, that are not under legal protection, and that are already deforested so that coffee farming could make a positive contribution to landscape restoration.